Effectiveness Rinse with Infused Pondoh Snakefruit on Redusing the OHIS Value in Elementary School Batukerbuy IV Pamekasan 2019 - Syawaludin Ardy Syahputra; Endang Purwaningsih; Soesilaningtyas Soesilaningtyas (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2020)
ABSTRACTThe Directorate of Dental Health (2000) sets a long-term goal of the Dental and Oral Health program, which is an optimal degree of oral health with a measure of oral hygiene in elementary school students with an Oral Hygiene Index Simplified (OHIS) range of 0.6-1.2 . Initial examination at Elementary School Batukerbuy IV Pamekasan, OHIS values were obtained with an average of 3.1. The purpose of this study was to determine the effectiveness of gargling with 20% infused of pondoh snakefruit on OHIS scores fourth students of Elementary School Batukerbuy IV Pamekasan. This research method is quasy experiment using the Pre and Post-test design with control group design. Respondents were selected by the total quota sampling method in fourth students of Elementary School Batukerbuy IV Pamekasan who were 10 years old and obtained respondents as many as 40 people. Based on the results of data analysis, there is an insignificant difference in average values between after rinsing infused pondoh snakefruit 20% by 19.03 and chlorhexidine mouthwash 0.2% with an average value of 21.98 and a difference of 2.95. Based on research that has been done, it was concluded that rinse chlorhexidine mouthwash 0.2% was more effective in reducing the OHIS value compared to rinse infused of pondoh snakefruit 20%. Keywords: OHIS; infused pondoh snakefruit; elementary school students